"The marketing value added to print variable designs by Ink Jet ( application on the ceramic market)" - Galal Salam; Mona Ali; Maha Abdel Fatah (Journal of Architecture, Art & Humanistic Science, 2018)
This research is divided into two axes, the first axis: -which includes the theoretical study to present the importance of the Ink-Jet printing and the role of marketing management in the ceramic companies, the second axis: - includes the applied study to determine the added value of marketing management when presenting the idea of  Print your design on ceramic customers in the market of  great Cairo. The theoretical axis reviewed the importance of Ink-Jet printing in the ceramic industry and achieving the required quality, and maintaining the marketing efficiency of the company, clarifying the color range of the inks in ink-jet printing for ceramics, and the role of ink-jet printing to raise the marketing value by explaining (the role of marketing management - the Factory that affect on the size of the administrator inside the administrative structure of the marketing - the Factory that affect on the success of the idea Print your design in the world of ceramics).    The application focused on the work of a questionnaire directed to the marketing management -for some of the leader companies in the field of ceramic manufacturing and marketing centers, and Submit it to 10 marketing departments, the questionnaire included six questions to measure the role of marketing management in the company and to know if the experiment of Print Your design is still An application  or not been accepted until now by the customer . The researcher reached to the most important practical results: 1-   The marketing management in any company shall endeavor to study the market and satisfy the desires of the customers and study the competitors. The decision is left to the customer, according to the decision satisfies and achieves his requirements. 2-   The ceramic printing market depends on the ink-jet printing technology for its high quality. 3-   The idea of Print your own design on ceramics did not succeed, which was applied by one of the ceramic companies in the Egyptian market -  and when direct the question directly to marketing managers The answers were as follows: A - Although the idea of printing your own design on the ceramics is inexpensive, but it has not received the acceptance of customers because the customers confidence in the company offers. B - To implement the idea to print your design on the ceramics I require the order of running at least 3000 square meters for one design. 4- The weakness of the marketing value added to the printing of the variable designs by ink-jet printing - this means the customer's confidence in the design of the product (ceramic) submitted to him by the company chosen.